Penerapan Restorative Justice sebagai Inovasi Penyelesaian Kasus Tindak Pidana Ringan - Iklimah Dinda Indiyani Adiesta (INTERDISCIPLINARY JOURNAL ON LAW, SOCIAL SCIENCES AND HUMANITIES, 2021)
Abtract This paper aims to analyze the handling of minor crimes with the conventional justice system and test the chances of restorative justice applied as an innovation in the settlement of minor criminal cases. Public disillusionment with the implementation of criminal proceedings led to the insistence on reforming the solution. The handling of minor crimes with the conventional justice system, judged not to reflect a sense of justice. The inequality of understanding the value of losses and the amount of fines makes the basis of a criminal act can be categorized as a minor crime between the police, prosecutors and courts raises a bad stigma regarding the handling of minor crimes today, in addition, the handling of minor crimes that do not maximize settlements oriented to the recovery of victim losses such as restorative justice. This research uses juridical-normative methods with conceptual and statutory approaches. The authors of this study used primary legal materials derived from legislation as well as secondary ones derived from books and legal journals relevant to the discussion. Then to enrich the references to this study, the authors used non-legal materials. This study shows that, the handling of minor crimes using the conventional justice system does not show the principle of proportionality in basing the category of a criminal act can be said to be a minor crime if looking at Perma No.2 Year 2012. In addition, the implementation of Perma, not maximum and the imposing of prison sanctions against perpetrators of minor crimes are ineffective. With such conditions, restorative justice can be used as an innovation in the settlement of minor criminal cases, because it has fulfilled all the requirements for a criminal act resolved by restorative justice. Keywords: Minor Crimes, Restorative Justice, Conventional Justice System